Criminological analysis of the individual victims of sexual crimes, and its behavior - Ларченко, Марина Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
The article defines the nature of the relationship the offender to the victim of a sexual offense, whichsignificantly affects the motivation of the criminal manifestations. Trace the influence of the social bond betweenthem on the type and degree of violence, and personal characteristics of the victim to the level of victimization.